Awareness of Breast Self-Examination among Female Community Health Volunteers of Pokhara - Koirala, Dipti; Silwal, Muna; Pokhrel, Sushila; Adhikari, Ramesh (Journal of Nepal Health Research Council, 2023)
Background: Breast self-examination is a simple, inexpensive and effective method of examining the breast by woman herself after 20 years of age in order to detect a breast lump in the early stage. Women should have this knowledge for early detection and treatment of breast cancer. So, the present study aimed to assess awareness of female community health volunteers regarding breast self-examination and the effect of a teaching program. Methods: One group pre-test post-test study was conducted among 145 female community health volunteers selected from eight wards of Pokhara Metropolitan using convenient sampling technique. Data was collected using a self-administered questionnaire from 27 March to 23 April 2022. Descriptive and inferential statistics were used for data analysis. Results: Before intervention, around two third of respondents (67.6%) had inadequate and only 1.4% had adequate level of awareness. But after the intervention, 68.3% had adequate level of awareness. The post-test mean awareness score (23.87 ± 4.7) was higher than pre-test mean awareness score (12.97 ± 3.93). Test of significance revealed that increment in the awareness due to a structured teaching program was highly significant (p <0 .001). This study also found that there was difference in the mean pretest awareness score according to educational level of the respondents only. Based on the mean score, the score was significantly higher among women with higher level of education (p=<.001). Conclusions: Around two thirds of female community health volunteers have inadequate level of awareness regarding breast self-examination before the intervention. Educational intervention program was found to be effective in improving their awareness. Keywords: Awareness; breast; self-examination